2016
DOI: 10.1097/sap.0000000000000564
|View full text |Cite
|
Sign up to set email alerts
|

An Algorithm for Forefoot Reconstruction With the Innervated Free Medial Plantar Flap

Abstract: The innervated free medial plantar flap is an attractive and feasible option for coverage of medium-to-large defects of the plantar forefoot in the hands of a skilled microsurgeon. It has a place in our algorithmic approach to forefoot reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Complex soft tissue defects of the foot and ankle caused by trauma, infection, tumor cancer or diabetes are common and can be accompanied by exposed tendons, neurovascular bundles and bone. There are multiple options for the reconstruction of complex soft tissue defects in these areas, including the use of both pedicled flaps and free flaps (e.g., a lateral supramalleolar flap [2], a peroneal artery perforator flap [3,4], posterior tibial artery perforator flap [5], a sural neurocutaneous/neurofasciocutaneous flap [6,7,8], a medial pedis flap [9], a dorsal metatarsal flap [10], a dorsalis pedis flap [11], a pedicled or free medial plantar flap [12,13], a free groin flap [14,15], a free anterolateral thigh perforator flap [16,17,18], or a free anteromedial thigh perforator flap [19]). In addition, the successful reconstruction of complex soft tissue defects of the foot and ankle is critical because of the unique standing, weight-bearing and walking functions of the foot.…”
Section: Introductionmentioning
confidence: 99%
“…Complex soft tissue defects of the foot and ankle caused by trauma, infection, tumor cancer or diabetes are common and can be accompanied by exposed tendons, neurovascular bundles and bone. There are multiple options for the reconstruction of complex soft tissue defects in these areas, including the use of both pedicled flaps and free flaps (e.g., a lateral supramalleolar flap [2], a peroneal artery perforator flap [3,4], posterior tibial artery perforator flap [5], a sural neurocutaneous/neurofasciocutaneous flap [6,7,8], a medial pedis flap [9], a dorsal metatarsal flap [10], a dorsalis pedis flap [11], a pedicled or free medial plantar flap [12,13], a free groin flap [14,15], a free anterolateral thigh perforator flap [16,17,18], or a free anteromedial thigh perforator flap [19]). In addition, the successful reconstruction of complex soft tissue defects of the foot and ankle is critical because of the unique standing, weight-bearing and walking functions of the foot.…”
Section: Introductionmentioning
confidence: 99%
“…Regional flaps, pedicled flaps, and free flaps might be used, but the most ideal flap is one that covers the heel with a skin texture similar to that of the sole. The most widely accepted flap that has similar characteristics to the sole is a medial plantar artery flap, which several authors have reported as yielding satisfactory results (Acikel et al, ; Koshima et al, ; Miyamoto et al, ; Oh, Moon, Cha, Koh, & Chung, ; Trevatt et al, ; Wan et al, ; Yang et al, ; Zelken & Lin, ). The elevation of the medial plantar flap involves the medial plantar nerve and its cutaneous branches for the sensory restoration of the flap.…”
Section: Discussionmentioning
confidence: 99%
“…The peroneal artery perforator (PAP) flap provided a thin and pliable skin [4]. Based on our previous experience, using it in the distal hand and foot reconstruction, we successfully transferred [18]. Size discrepancy was encountered between donor vein graft and recipient artery, which increased the chance of thrombosis.…”
Section: Discussionmentioning
confidence: 99%